Chemotherapy-Induced Upregulation of Somatostatin Receptor-2 Increases the Uptake and Efficacy of (177)Lu-DOTA-Octreotate in Neuroendocrine Tumor Cells - Shah, Rashmi G. (Cancers (Basel), 2021)
SIMPLE SUMMARY: The peptide receptor radionuclide therapy (PRRT) with (177)Lu-DOTA-octreotate (LuTate) is recommended for neuroendocrine tumors (NETs) which overexpress somatostatin receptors (SSTR). A combination of LuTate with chemotherapy improves its objective response in NET patients, and here we characterized chemotherapy-induced upregulation of SSTR2 receptors as a cause for this improved response to LuTate. Using multiple NET and non-NET cell lines, we examined the SSTR2 expression for up to 7 days after exposure to drugs and its effect on LuTate uptake and cell proliferation. We report that the exposure to varying doses of chemotherapeutic drugs such as temozolomide for 24 h or 5 days results in upregulation of SSTR2 receptors between 3–7 days. This effect is more pronounced in low SSTR2 expressing BON-1 cells than in high SSTR2 expressing NCI-H727 or non-NET cancer or non-cancer cells. Thus, a properly-timed pre-treatment with low doses of chemotherapy could improve therapeutic efficacy of LuTate in NET patients. ABSTRACT: The peptide receptor radionuclide therapy (PRRT) with (177)Lu-DOTA-octreotate (LuTate) is recommended for different types of neuroendocrine tumors (NETs) which overexpress somatostatin receptors (SSTR). A combination with chemotherapy improves objective response to LuTate in NET patients and here we characterized chemotherapy-induced upregulation of SSTR2 receptors as a cause for this improved response to LuTate. The NET cell lines with low (BON-1) or relatively high (NCI-H727) SSTR2-expression levels, and non-NET cancer and normal cells were treated with chemotherapeutic drugs and assessed for upregulation of SSTR2. We report that an exposure to low or high doses of drugs, such as temozolomide for 24 h or 5 day results in upregulation of SSTR2 between 3–7 days, increased LuTate uptake and decreased rate of cell proliferation. This effect is at the level of SSTR2-mRNA and is more pronounced in low SSTR2 expressing BON-1 than in high SSTR2 expressing NCI-H727 or non-NET cancer or normal cells. Thus, a properly timed pre-treatment with low-dose chemotherapy could not only improve therapeutic efficacy of LuTate in NET patients who are presently eligible for PRRT, but also allow PRRT to be administered to patients with low SSTR-expressing NETs, who would otherwise not respond to this modality because of insufficient radiation delivery.